Vocabulary development. The macmillan spectrum of skills, level 3 / Lee C. Deighton - Deighton, Lee C. (1964)
How your vocabulary grows make your vocabulary, the meanings of base words, suffixes help us build words, the e that disappears and the l that doesn't. double the consonant, when y becomes I, some suffixes add meaning to base words, using the dictionary more work, finding the right dictionary meanings, watching words change in meaning, how we find word meanings, how context helps, using word parts and context together.